Identification of Features for the City Branding: The Case of Shusha City, Azerbaijan as Tourism Destination - HUSEYNLI, Bahman (Journal of Environmental Management and Tourism, 2023)
The main purpose of this study is to investigate the strategic importance of the creation of the city brand of Shusha, the cultural capital of Azerbaijan, based on the studies in the literature, and to determine the branding elements. The study was prepared in accordance with the methodology of qualitative research methods and is exploratory research. Systematic approach, synthesis and induction methods were used in the study. The branding of Shusha as a city of music, architecture, heroism, and culture is one of the results of the research. As a result of the study, the brand elements that can be used in the branding of the city of Shusha in Azerbaijan were tried to be determined. Brand elements that can be used in the branding of Shusha are Kharibulbul flower (Ophrys Caucasica), Karabakh horses, Shusha fortress, Govhar Agha mosque, mugham, carpet art, famous people. The creation of the Shusha city brand can make it one of the world's tourism destinations.